Banana Roll : “Pemanfaatan Pisang Di Masamba Menjadi Cemilan Yang Bikin Nagih Dan Bernilai Jual”: Banana Roll: Utilization of Bananas in Masamba as a Snack that Makes You Addicted and is Worth Selling - Maudi Dian Tairas; Oki anggara; Della Saputri; Afiq Azizah; Mardian; Lutfiyah Maharani; Dingse Pandiangan (Sam Ratulangi University, 2024)
Utilizing bananas to make banana roll snacks makes you addicted. The aim of making this Banana roll product is to generate creativity and motivation in the community in managing the harvests of banana farmers in North Luwu which can be of marketable value. This Banana Roll product is made using a type of plantain that has the advantage of a natural sweet banana taste. Bananas contain fiber, protein, minerals, potassium, antioxidants, and vitamins which are useful for speeding up metabolism, increasing immunity, treating anemia, losing weight, and healthy bones. Banana Roll is one of the processed Banana Roll products that uses four methods in making them, namely input, process, output, and evaluation. Banana Roll is an example of creative innovation that turns Masamba bananas into an interesting and marketable snack. By utilizing local ingredients and combining them with spring roll skins and a variety of fillings, we can create products that are appetizing and suitable for both local and international markets. Conclusion The use of bananas in snacks with high selling value can provide skills to the community and to be innovative and creative in managing bananas. ABSTRAK Pemanfaatan pisang menjadi olahan cemilan Banana Roll yang bikin nagih. Tujuan pembuatan produk Banana Roll ini adalah membangkitkan kreatifitas dan motivasi masyarakat dalam mengelolah hasil panen para petani pisang di Luwu Utara yang dapat bernilai jual. Pembuatan produk Banana Rollini menggunakan jenis pisang raja yang mempunyai keunggulan rasa manis pisang alami. Pisang memiliki kandungan serat, protein, mineral, potansium, antioksidan dan vitamin yang bermanfaat untuk memperlancar metabolisme, meningkatkan kekebalan tubuh, mengatasi anemia, menurunkan berat badan dan menyehatkan tulang. Banana Roll merupakan salah satu olahan dari produk pisang yang dalam pembuatannya terdapat empat metode yaitu input, proses, output dan evaluasi. Banana Roll adalah contoh inovasi kreatif yang mengubah pisang Masamba menjadi cemilan yang menarik dan bernilai jual. Dengan memanfaatkan bahan lokal dan menggabungkannya dengan kulit lumpia serta variasi isian, kita dapat menciptakan produk yang menggugah selera dan cocok untuk pasar lokal maupun internasional.Kesimpulan pemanfaatan pisang menjadi cemilan yang bernilai jual tinggi dapat memberikan keterampilan kepada masyarakat dan untuk inovatif dan kreatif dalam mengelolah pisang.